International collaboration, funding and association with burden of disease in randomized controlled trials in Africa - George H. Swingler; Victoria Pillay; Elizabeth D. Pienaar; John P.A. Ioannidis (The World Health Organization, 2005)
OBJECTIVE: This study aimed to assess whether randomized controlled trials conducted in Africa with collaborators from outside Africa were more closely associated with health conditions that have a burden of disease that is of specific importance to Africa than with conditions of more general global importance or with conditions important to developed countries. We also assessed whether the source of funding influenced a study's relevance to Africa. METHODS: We compared randomized controlled trials performed in Africa that looked at diseases specifically relevant to Africa (as determined by burden of disease criteria) with trials classified as looking at diseases of global importance or diseases important to developed countries in order to assess differences in collaboration and funding. FINDINGS: Of 520 trials assessed, 347 studied diseases that are specifically important to Africa; 99 studied globally important diseases and 74 studied diseases that are important to developed countries. The strongest independent predictor of whether a study was of specifically African or global importance was the corresponding author's country of origin: African importance was negatively associated with a corresponding author being from South Africa (odds ratio (OR) = 0.04; 95% confidence interval (CI) = 0.02-0.10) but there was little difference between corresponding authors from other African countries and corresponding authors from countries outside Africa. The importance of a study to Africa was independently associated with having more non-African authors (OR per author = 1.31; 95% CI = 1.08-1.58), fewer trial sites (OR per site = 0.69; 95% CI = 0.50-0.96), and reporting of funding (OR = 2.14; 95% CI = 1.15-4.00). Similar patterns were present in the comparisons of trials studying diseases important to Africa versus those studying diseases important to developed countries with stronger associations overall. When funding was reported, private industry funding was negatively associated with African importance compared with global importance (OR = 0.31, P = 0.008 for African importance and OR = 0.51, P = 0.57 for importance for developed countries). CONCLUSION: The relevance to Africa of trials conducted in Africa was not adversely affected by collaboration with non-African researchers but funding from private industry was associated with a decreased emphasis on diseases relevant to Africa.